2012
DOI: 10.1093/bja/aer500
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of patterns of three-phase bone scintigraphy for patients with complex regional pain syndrome diagnosed using the proposed research criteria (the ‘Budapest Criteria’)

Abstract: The diagnostic value of a positive TPBS for CRPS is low from the view point of the Budapest research criteria. Our findings suggest that a diagnosis of CRPS using the Budapest research criteria should be considered when decreased patterns of TPBS are observed during Phases I and II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 26 publications
0
13
0
2
Order By: Relevance
“…Moreover, 3 prospective studies have been also published [26,27,30] confirming the usefulness of TBPS as additional tool in doubtful cases [30] and when the duration of the pathology is shorter than 3 [26] or 5 months [27]. Two other retrospective studies [36,37] using the Budapest criteria were also recently published. Moon et al [36], found a low utility of TBPS for diagnosis of CRPS and AlSharif et al [37] found a positive scintigraphy in patients with vasomotor symptoms, motor and/or trophic changes, with a duration of less than 3 months.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, 3 prospective studies have been also published [26,27,30] confirming the usefulness of TBPS as additional tool in doubtful cases [30] and when the duration of the pathology is shorter than 3 [26] or 5 months [27]. Two other retrospective studies [36,37] using the Budapest criteria were also recently published. Moon et al [36], found a low utility of TBPS for diagnosis of CRPS and AlSharif et al [37] found a positive scintigraphy in patients with vasomotor symptoms, motor and/or trophic changes, with a duration of less than 3 months.…”
Section: Discussionmentioning
confidence: 94%
“…Two other retrospective studies [36,37] using the Budapest criteria were also recently published. Moon et al [36], found a low utility of TBPS for diagnosis of CRPS and AlSharif et al [37] found a positive scintigraphy in patients with vasomotor symptoms, motor and/or trophic changes, with a duration of less than 3 months. In our study, TBPS was also particularly helpful when it was performed in the first 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…[46] The sample size ranged from 13 to 145 patients (Table 1), mean age from 35 to 63 years, and the average disease duration from 6 to 103 weeks. The reference standard for the diagnosis of CRPS was in three studies the clinical Budapest criteria, [29, 44, 45] four studies the IASP criteria, [34, 42, 43, 47] and in five studies the Kozin diagnostic criteria. [40, 41, 46, 48, 49] Seven studies [3032, 3638] did not report on the diagnostic criteria used for the diagnosis of CRPS 1 and two studies [33, 39] used other clinical criteria In total 13 studies were included in the analysis of the influence of patient characteristics on the proportion of positive bone scans.…”
Section: Resultsmentioning
confidence: 99%
“…While some studies support the use of BS for establishing the diagnosis of CRPS [29, 34, 42] others reported a low diagnostic value of a positive BS. [33, 44] In a recent review [57] the authors stated that little emphasis is given to the typical imaging and advocated for the use of BS to support the clinical diagnosis. In a meta-analysis BS was compared to MRI for the diagnosis of CRPS 1 and found a higher sensitivity of BS compared to MRI and a comparable specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Danach wäre eine positive Drei-Phasen-Knochenszintigrafie unterstützend für die klinische CRPS-Diagnose, sie kann jedoch schlecht von anderen Ursachen der Mehranreicherung im Knochen unterscheiden. Laut einer aktuellen Arbeit war die Spezifität für das CRPS sogar höher, wenn in allen 3 Phasen oder zumindest in den ersten beiden Phasen eine verminderte Aufnahme des Tracers nachweisbar war [19]. Auch konventionelle Röntgenaufnahmen sind nicht geeignet, in der Frühphase nach einem Trauma ein CRPS zu diagnostizieren [20].…”
Section: Klinisches Bildunclassified